Flexible Time to Enhance Shopping Need and Customer Visit on the Shopee Website - Sari, Dian Ratna; Indriastuti, Herning; Rahmawati, Heni Rahayu (Indonesian Journal of Advanced Research, 2025)
This study aims to analyze the effect of flexible time on shopping need and customer visit on the Shopee platform. Using a quantitative approach with SEM-PLS, the findings reveal that flexible time directly and indirectly influences customer visits through shopping need. The results support the Stimulus-Organism-Response (SOR) model in explaining digital consumer behavior. Flexible time enhances psychological comfort and internal motivation to shop and engage with the platform. The study implies that time-based marketing strategies in e-commerce are essential to boost user engagement and loyalty.